THE PETROLEUM GENERATION POTENTIAL AND EFFECTIVE OIL WINDOW OF HUMIC COALS RELATED TO COAL COMPOSITION AND AGE - Petersen H.I. (My University, 2006)
A worldwide data set of more than 500 humic coals from the major coal-forming geological periods has been used to analyse the evolution in the remaining (Hydrogen Index, HI) and total (Quality Index, QI) generation potentials with increasing thermal maturity and the 'effective oil window' ('oil expulsion window'). All samples describe HI and QI bands that are broad at low maturities and that gradually narrow with increasing maturity. The oil generation potential is completely exhausted at a vitrinite reflectance of 2.0-2.2%R o or T max of 500-510 °C. The initial large variation in the generation potential is related to the original depositional conditions, particularly the degree of marine influence and the formation of hydrogen-enriched vitrinite, as suggested by increased sulphur and hydrogen contents. During initial thermal maturation the HI increases to a maximum value, HI max. Similarly, QI increases to a maximum value, QI max. This increase in HI and QI is related to the formation of an additional generation potential in the coal structure. The decline in QI with further maturation is indicating onset of initial oil expulsion, which precedes efficient expulsion. Liquid petroleum generation from humic coals is thus a complex, three-phase process: (i) onset of petroleum generation, (ii) petroleum build-up in the coal, and (iii) initial oil expulsion followed by efficient oil expulsion (corresponding to the effective oil window). Efficient oil expulsion is indicated by a decline in the Bitumen Index (BI) when plotted against vitrinite reflectance or T max. This means that in humic coals the vitrinite reflectance or T max values at which onset of petroleum generation occurs cannot be used to establish the start of the effective oil window. The start of the effective oil window occurs within the vitrinite reflectance range 0.85-1.05%R o or T max range 440-455 °C and the oil window extends to 1.5-2.0%R o or 470-510 °C. For general use, an effective oil window is proposed to occur from 0.85 to 1.7%R o or from 440 to 490 °C. Specific ranges for HI max and the effective oil window can be defined for Cenozoic, Jurassic, Permian, and Carboniferous coals. Cenozoic coals reach the highest HI max values (220-370 mg HC/g TOC), and for the most oil-prone Cenozoic coals the effective oil window may possibly range from 0.65 to 2.0%R o or 430 to 510 °C. In contrast, the most oil-prone Jurassic, Permian and Carboniferous coals reach the expulsion threshold at a vitrinite reflectance of 0.85-0.9%R o or T max of 440-445 °C. © 2006 Elsevier B.V. All rights reserved.
Keywords: BITUMEN INDEX; DEPOSITIONAL CONDITIONS; GENERATION POTENTIAL; HUMIC COALS; HYDROGEN INDEX; OIL WINDOW; QUALITY INDEX; Jurassic; Permian; Carboniferous; Mesozoic::Jurassic; Мезозой::Юрская; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Carboniferous; Палеозой::Каменноугольная